MAPPING THE EVOLUTION AND CURRENT TRENDS HUMANISTIC PEDAGOGIC: BIBLIOMETRIC ANALYSIS - Huda, Miftakul Huda; Siswanto, Budi Nur Siswanto; Utama, RD Dian; Christianingrum, Christianingrum; Komara, Esi Fitriani (Universitas Negeri Surabaya, 2023)
This bibliometric analysis is aimed at research on pedagogic humanism. Data sources were taken from the Scopus database, with the topic of discussion on Education and training, from searches for the words